EXCELLENCE OF KI HAJAR DEWANTARA’S CHARACTER EDUCATION FOR THE EDUCATION SYSTEM IN INDONESIA - Suyanto, Suyanto; Jumintono, Jumintono (SYNTIFIC, 2025)
Background. The era of globalization is full of competition, so education needs to be based on quality to produce superior human resource development. The quality of education graduates is related to the characteristics determined by educational institutions and shows the readiness of graduates to plunge and work directly in the community and the world of work as expected by stakeholders. Research Purpose. The purpose of this study is to describe Ki Hajar Dewantara's character education as an excellence in education management in Indonesia. Research methods. This research collected literature from various databases from Google Scholar, DOAJ, and Research Gate related to Ki Hajar Dewantara's character education. The keywords in this literature review, according to the PICO framework, are P: character education, I: Ki Hajar Dewantara, C: other character education theories, and O: excellence. The three main components of data analysis: data reduction, data presentation, and conclusion drawing. Findings. There were 6 articles relevant to this research topic out of 218 articles that were assessed and analyzed Ki Hajar Dewantara's character education has a positive influence on Indonesia's strong education system that creates a diverse and high-quality generation, from the contemporary to the digital era as it is today. Conclusion. The excellence of Ki Hajar Dewantara's character education reflects the unique characteristics of society and culture, fostering the nation's character, including honesty, courtesy, intelligence, spirituality, and leadership spirit, fostering a culture of mutual tolerance for diversity in Indonesia and mutual dependence on one another.